(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Globalization, changes in technology, as well as socio economic changes presuppose dynamic challenges, which, in their turn, demand an organizational change. However, the attempts to change could not become effective without the formation of the strategic communication methods that then should enhance the most available level of transparency, inclusion, and interest towards staff. The paper discusses the way communication can support the conversion of change within an organization with particular regard to the delivery of goal number eight sustainable development (Decent Work and Economic Growth). The research takes a qualitative, desk-based form of research where the author identifies with the existing literature on topics in which he identifies on communication tactics (storytelling, internal branding, dialogue and Internet platforms) that may reduce the process of resistance in creating trust and respect to dignity in communication processes of change within the consumer realm at the workplace. The findings demonstrate communications as one of the main factors in organizational performance and core values and principles of decent work and must ensure human-focused, equitable and sustainable changes. The conclusion of the paper is that communication strategies when implemented in change management are beneficial to the organization and enhance international efforts to promote decent work to every person.